Gingival recession: prevalence and risk indicators among young greek adults - Chrysanthakopoulos, Nikolaos A. (Medicina Oral S.L., 2014)
Objectives: The aim of the current research was to assess the prevalence of gingival recession and to investigate possible associations among this condition, periodontal and epidemiological variables in a sample of young Greek adults in a general dental practice. Material and Methods: A total of 1,430 young adults was examined clinically and interviewed regarding several periodontal and epidemiological variables. Collected data included demographic variables, oral hygiene habits and smoking status. Clinical examination included the recording of dental plaque, supragingival calculus presence, gingival status and buccal gingival recession. Multivariate logistic regression analysis model was performed to access the possible association between gingival recession and several periodontal and epidemiological variables as potential risk factors. Results: The overall prevalence of gingival recession was 63.9%. The statistical analysis indicated that higher educational level [OR= 2.12, 95% CI= 0.53-8.51], cigarette smoking [OR= 1.97, 95% CI= 1.48-7.91], frequent tooth brushing [OR= 0.98, 95% CI= 0.56-1.96], presence of oral piercing [OR= 0.92, 95% CI= 0.38-1.58], presence of gingival inflammation [OR= 4.54, 95% CI= 1.68-7.16], presence of dental plaque [OR= 1.67, 95% CI= 0.68-2.83] and presence of supragingival calculus [OR=1.34, 95% CI= 0.59-1.88], were the most important associated factors of gingival recession. Conclusions: The observations of the current research supported the results from previous authors that several periodontal factors, educational level and smoking were significantly associated with the presence of gingival recession, while presence of oral piercing was a new factor that was found to be associated with gingival recession. Key words:Gingival recession, prevalence, risk factors, young adults.